Cognitive biases: potential behavioral marker for future development of postpartum depression and childbirth-related post-traumatic stress disorder - Cywiak, Vanessa; Solt, Ido; Givon-Benjio, Nur; Fruchter, Eyal; Okon-Singer, Hadas (Frontiers in Psychiatry, 2025)
Postpartum Depression (PPD) and Childbirth Post-Traumatic Stress Disorder (CB-PTSD) are psychiatric conditions that cause significant distress. Yet despite their high prevalence and decades of research, knowledge about causal cognitive mechanisms that may assist in predicting or preventing these conditions is still missing. One characteristic of PPD and CB-PTSD that may contribute to their early prevention is the existence of cognitive biases concerning future parenting. Cognitive biases have been shown to play an important role in the etiology of various other psychiatric disorders, including depression and PTSD, suggesting they might have a similar role in PPD and CB-PTSD. From a theoretical perspective, understanding the associations between cognitive biases, PPD, and CB-PTSD may lead to novel theoretical models and research avenues. Additionally, understanding the cognitive mechanisms underlying PPD and CB-PTSD has several important clinical implications, such as early detection, preventative care, and developing individually tailored cognitive therapies focusing on these specific biases.